2017
DOI: 10.5468/ogs.2017.60.3.308
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermic intrathoracic chemotherapy with cisplatin for ovarian cancer with pleural metastasis

Abstract: Intrathoracic metastasis of ovarian cancer has poor prognosis regardless of treatment modality. Recent development of surgical techniques and the new concept of direct infusion of chemotherapeutic agents with hyperthermia could help with the treatment of disseminated diseases in ovarian cancer. Using video-assisted thoracoscopic surgery and intracavitary chemotherapy with hyperthermia, we tried hyperthermic intrathoracic chemotherapy for a case of stage IV high-grade serous ovarian cancer with pleural metastas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The purpose of the 13th study was to examine the effectiveness of repeated intrapleural chemotherapy through a port system and report only the survival rate of the included patients 17 . Four studies reported no toxicity after the intrapleural chemotherapy 14,17,20,22 . In the complete cohort of 497 patients, 11 cases of myelosuppression and another 18 cases of other grade 3/4 toxicity were described.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of the 13th study was to examine the effectiveness of repeated intrapleural chemotherapy through a port system and report only the survival rate of the included patients 17 . Four studies reported no toxicity after the intrapleural chemotherapy 14,17,20,22 . In the complete cohort of 497 patients, 11 cases of myelosuppression and another 18 cases of other grade 3/4 toxicity were described.…”
Section: Resultsmentioning
confidence: 99%
“… 17 Four studies reported no toxicity after the intrapleural chemotherapy. 14 , 17 , 20 , 22 In the complete cohort of 497 patients, 11 cases of myelosuppression and another 18 cases of other grade 3/4 toxicity were described. One study established the levels of intrapleural toxicity of docetaxel.…”
Section: Resultsmentioning
confidence: 99%
“…HIPEC with cytoreduction has demonstrated prolonged survival for pseudomyxoma peritonei (14). Isolated reports of debulking and HITHOC have been described with some success for both pseudomyxoma peritonei and ovarian carcinoma (15)(16)(17)(18)(19).…”
Section: Current Use Of Hithoc For Metastatic Diseasementioning
confidence: 99%